SPP PAYMENT PROGRAM APPLICATION ON SAKURA GROUP PLAY USING MICROSOFT ACCESS 2000 - Indah Ekowati; Sutarno Sutarno, SKom, MMSi (Jurnal Sistem Informasi, 2008)
In scientific writing, the writer wanted to try to make an application program that is calculating the payment of fees at Sakura Play Group by using the computerized system. The process of administration at a school that is generally still manual, so that in the process of payment of common errors in data recording payments. This process is no longer sufficient at this time that's necessary for computer systems. With existence of computerized system to calculate payments can ease the administrative part in the operation and minimize errors that may occur, as well as facilitate in making financial reports at the headmaster.